Origin myths among the mountain peoples of the Philippines - Beyer, Henry Otley 1883-1967; Barton, Roy Franklin 1883-1947 (Public Domain, 1913)
This article is a comparative study and presentation of the texts of several origin myths among five cultural groups (Ifugao, Tagbanua, Igorot, Manobo, and Bontoc) of the Mountain Province in Luzon. Similarities in religious beliefs, cosmology, and mythological themes are noted, including description of hero figures, deities, and their activities. The author contrasts the Kiangan Ifugao and Central Ifugao and proposes that the similarities between the two are due to mixing of ideas of ancient cultures while the differences are due to 'survivals.' Thus, the 'distinctly composite Ifugao group' of today is the result of coalescence of divergent ancient cultures.